Patients’ related sexual outcomes in colorectal surgery - Liot, Emilie; Christou, Niki; de Sousa, Sandra; Klein, Jacques; Pouya, Iranmanesh; Guedj, Danae; Buchs, Nicolas C.; Ris, Frédéric (Frontiers in Oncology, 2022)
Background: Patients undergoing colorectal surgery (CRS) have an increased risk of developing sexual disorders, attributed to different mechanisms. In this context, sexual function (SF) assessment of patients before and after surgery is essential: to identify risk factors for sexual disorders as well as to minimize their impact on overall quality of life (QoL) allowing them a satisfying relationship and sexual life. Material and Methods: Patients over 18 years who underwent a CRS in the University Hospital of Geneva, Switzerland, between June 2014 and February 2016 were included. Our main objective was to compare and analyze the evolution of SF, QoL and marital satisfaction (MS) before and after CRS. Specific and standardized tests were used. Results: A cohort of 72 patients with a median age of 58.73 was analyzed. The majority of CRS was elective (91.5%). 52.8% of patients underwent surgery for oncological reasons. There was no statistical difference of SF, sexual QoL and MS before and after elective or emergency CRS for men. Interestingly, a significant decrease of women’s SF (FSFI) as well as their satisfaction within their couple (Locke-Wallace) until 12 months after surgery was found (p=0.021). However, they showed a steady SF (GRISS) within their couple until 12 months after surgery. Conclusion: Regarding the knowledge about difficulties to talk about this intimate topic and gender differences, this general overview raises the question of the necessity to introduce in a long-course follow-up different methods of sexual health assessment with specific stakeholders.